Chine : une transition salariale à hauts risques - Muriel Périsse (Revue de la Régulation)
A growing category of rightless workers has been developping during the reforms in China : powerless wage-earners whose origin must be found in the obstacles to the enforcement of labour and social laws, and in the difficulties to built bargained solutions to the highly adversarial industrial relations. The risks related to this wage-earning relationship, only based on the balance of strength, have to be considered as the implicit results of the reforms themselves, and not as the temporary outcomes of the transition period. The path through the wage-earning society suffers from the lack of labour market intermediary institutions. If conflict drives the dynamics of the wage-earning relationship rules, the situation today demonstrates that it may be very problematic to built up a specific social compromise able to support a regular capital accumulation.